Pengaruh Asset Growth dan Total Asset Turn Over terhadap Return On Asset pada Pt. HM Sampoerna Tbk Tahun 2006-2018 - Yulianta Yulianta; Jasmani Jasmani (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of Asset Growth and Total Asset Turn Over on Return On Assets at PT. HM Sampoerna Tbk Period 2016-2018. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study that Asset Growth has no significant effect on Return On Asset of 3.9%, the hypothesis test is obtained t count <t table or (-0.667 <2.201). Total Asset Turn Over has a significant effect on Return On Asset by 44.5%, hypothesis testing is obtained t count> t table or (2,967> 2,201). Asset Growth and Total Asset Turn Over simultaneously have a significant effect on Return On Assets, the regression equation Y = 13,030 + -0,232X1 + 9,431X2 is obtained and the determination value is 60.9%, the hypothesis test is obtained the value of F count> F table or (7,777> 3,710).